2007
DOI: 10.1080/10837450601166494
|View full text |Cite
|
Sign up to set email alerts
|

Percolation Theory and the Role of Maize Starch as a Disintegrant for a Low Water-Soluble Drug

Abstract: The objective of the present work is to investigate the presence or absence of a critical concentration of maize starch according to the percolation theory for a truly ternary system with respect to a minimum disintegration time. The results of this study show that the application of percolation theory is not limited to the study of binary systems. In this work it is shown how it can be used to analyze the behavior of binary and ternary systems for caffeine and mefenamic acid formulations containing a starch-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 13 publications
(21 reference statements)
0
14
0
Order By: Relevance
“…Appropriate processes can be readily developed based on such understanding to deliver desired performance. Following its initial introduction to pharmaceutical literature in 1980s,94, 95 the percolation theory has been shown useful in understanding powder compaction behavior of mixtures and in guiding tablet formulation design 96–104. More extensive applications of the percolation theory should contribute enormously to scientific formulation and process development.…”
Section: The Way Forwardmentioning
confidence: 99%
“…Appropriate processes can be readily developed based on such understanding to deliver desired performance. Following its initial introduction to pharmaceutical literature in 1980s,94, 95 the percolation theory has been shown useful in understanding powder compaction behavior of mixtures and in guiding tablet formulation design 96–104. More extensive applications of the percolation theory should contribute enormously to scientific formulation and process development.…”
Section: The Way Forwardmentioning
confidence: 99%
“…In recently published works, the application of percolation theory was expanded to investigation of key properties of pharmaceutical compacts,10–18 taking into account complex interactions of different processes involved in disintegration of complex multi‐particulate system. It is well known that heterogeneous ensembles like pharmaceutical formulations for solid dosage forms represent disordered particulate systems where it is necessary to take into account a geometrical description,19 that is, a topological modeling.…”
Section: Introductionmentioning
confidence: 99%
“…Percolation theory is, in fact, the most suitable tool to predict and simulate the geometrical phase transitions in a complex multi‐particulate system and allows finding the regions where the system undergoes transitional changes in its properties. In terms of solid dosage form design, such regions usually are linked to extreme values of drug dissolution rate, tablet disintegration time, tablet water uptake, etc 12, 14, 19–21. According to percolation theory, a transitional change happens at a critical concentration of components in a system when one component forms an infinite cluster propagating through the entire system (i.e., percolates).…”
Section: Introductionmentioning
confidence: 99%
“…The disintegration of tablets remains an important issue for the desirable release of the active pharmaceutical ingredient from a solid dosage formulation [19]. It has been reported that heterogeneous mixtures like pharmaceutical formulations for solid dosage forms demonstrate disarranged particulate systems where it is necessary to consider a geometrical representation, in other words, a topological modeling [17,20]. Geometrical phase transitions are independent of physical and chemical properties of the components, which enable the modeling.…”
Section: Discussionmentioning
confidence: 99%